A simple voxel-based assessment and visualization of dose to human for radiation protection using virtual simulation. (May 2018) - Li, Meng-kun; Liu, Yong-kuo; Peng, Min-jun; Xie, Chun-li; Yang, Li-qun
Abstract: In this paper, virtual simulation was taken as an auxiliary tool for radiation protection, dose assessment. So radiation protection using virtual reality was taken as a research subject. A simple voxel modeling for virtual human was proposed. Based on the voxel model, dose assessment and visualization methods for virtual human in radiation environment were proposed. The parallel technology contributed to dose assessment in real-time. Based on dose assessment and visualization methods, a radiation protection method using virtual simulation was developed for the preparation of working in radiation environment. These validation tests demonstrate these methods make it possible to plan for the exposure dose to workers in radiation environment using virtual simulation.